The Conundrum of Great Zimbabwe - Pikirayi, Innocent; Sulas, Federica; Chirikure, Shadreck; Chikumbirike, Joseph; Sagiya, Munyaradzi Elton (Journal of Urban Archaeology, 2023)
Abstract Great Zimbabwe (ad 1100-1700) was a substantial settlement comprising elite residences and non-elite housing, largely characterized by complexes of massive stone-walled structures. Its growth had an impact on energy resources within its immediate and broader environment, with water playing a key role in the development and persistence of the settlement. The settlement layout that extends beyond the monumental structures comprises water reservoirs and perimeter walls, which for several centuries sustained a substantial population living beyond the core urban area. This article sheds light on the ‘conundrum’ of Great Zimbabwe’s massive stone-built structures. A reconsideration of the functioning of Great Zimbabwe informs the conundrum, which is relevant to contemporary discussion on urban design, architecture, energy saving, and environmental sustainability.